تجربة تعليم اللغة العربية لأغراض خاصة في دولة ماليزيا: عرض وتقويم - Chik, Abdul Rahman (King Abdullah Bin Abdul Aziz International Centre for the Arabic Language, 2018)
The study covers the history of the academic research of Teaching Arabic for Specific Purposes (ASP) in Malaysia starting from late eighties of the last century. The report highlights ASP research activities, publications and language learning programs offered by Malaysian Higher Learning institutions.